Mechanochemical synthesis of non-stoichiometric copper sulfide Cu1.8S applicable as a photocatalyst and antibacterial agent and synthesis scalability verification. (4th October 2022) - Baláž, Matej; Augustyniak, Adrian; Tatykayev, Batukhan; Shalabayev, Zhandos; Burashev, Gairat; Dutková, Erika; Daneu, Nina; Briančin, Jaroslav; Balážová, Ľudmila; Tkáčiková, Ľudmila; Stahorský, Martin; Achimovičová, Marcela; et al.
Abstract : Digenite Cu1.8 S nanoparticles with photocatalytic and antibacterial activity were successfully prepared via one-step mechanochemical synthesis in a laboratory-scale and scalable fashion. Abstract : An effort to prepare different non-stoichiometric Cu x S y compounds starting from elemental precursors using mechanochemistry was made in this study. However, out of the 7 stoichiometries tested, it was only possible to obtain three phases: covellite CuS, chalcocite Cu2 S and digenite Cu1.8 S and their mixtures. To obtain the digenite phase with the highest purity, the Cu : S stoichiometric ratio needed to be fixed at 1.6 : 1. The reaction between copper and sulfur was completed within a second range, however, milling was performed for up to 15 minutes until the equilibrium in phase composition between digenite and covellite was reached. The possibility of preparing the product in a 300 g batch by eccentric vibratory milling in 30 minutes was successfully verified at the end. The estimated crystallite sizes for the digenite Cu1.8 S obtained via lab-scale and scalable experiments were around 12 and 17 nm, respectively. The obtained products were found to be efficient photocatalysts under visible light irradiation in the presence of hydrogen peroxide, being capable of the complete degradation of the Methyl Orange dye in a concentration of 10 mg L −1 in 2 hours. Finally, the antibacterial potential of both lab-scale and large-scale industrial products was proven and, regardless of the manufacturing scale, the nanoparticles retained their properties against bacterial cells.